Pengaruh Implementasi Enterprise Resource Planning dalam Supply Chain Management: Sebuah Tinjauan Literatur - Glorie Fajar Paularine; Amelia Setiawan; Hamfri Djajadikerta (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2025)
The implementation of Enterprise Resource Planning (ERP) systems in Supply Chain Management (SCM) has become an important strategy for companies across various industry sectors worldwide. ERP helps integrate various business functions into a coordinated system, enhancing operational efficiency and supporting a company's competitiveness in the global market. However, ERP implementation is not without challenges. High costs, resistance to change within organizations, and the complexity of integration with existing systems are major obstacles to implementation. The success of ERP implementation depends heavily on key factors such as strong support from top management, readiness of human resources, and selecting the right system according to the company's needs. Comprehensive training and effective change management are necessary to ensure employees can adapt to the new system. This study emphasizes the importance of regular evaluations to ensure the ERP system functions properly and delivers optimal benefits. Additionally, the research also suggests exploring more flexible ERP implementation strategies for small and medium-sized enterprises (SMEs), as well as integrating the latest technologies like artificial intelligence (AI) and blockchain to enhance supply chain efficiency. Further research is expected to provide new insights into best practices and innovations in ERP implementation across various industry sectors.